Identification of learning interests in biology learning in class X of SMK ISLAM AL AZHAR - Alexander, Alexander; Maharani, Lila; Jayawardana, Hepta Bungsu Agung (Universitas Khairun, 2025)
Education plays a crucial role in shaping human development and serves as the foundation for every citizen’s right to quality learning. Within the educational process, learning activities are central, and students’ interest in learning strongly influences academic success. This study aims to identify and measure students’ interest in learning biology at SMK Islam Al Azhar. The research was initiated in response to teachers’ concerns about the difficulty of assessing students’ learning interest, which affects the effectiveness of classroom instruction. A qualitative approach was adopted using three primary techniques: observation, interviews, and questionnaires. Participatory observations were conducted during lessons, followed by teacher interviews to validate the findings. Questionnaires based on established indicators of learning interest were then distributed to students. The results showed that the average questionnaire score among 20 active students was 72%, indicating a moderate level of learning interest. These results were supported by the data obtained from interviews and observations. Overall, the findings suggest that Grade X students at SMK Islam Al Azhar exhibit a moderate level of interest in biology, highlighting the need for innovative teaching strategies to enhance student motivation and engagement in science learning.